Comparative regionalization of Northern Eurasia by woody plants and ground vertebrates - Yu. S. Ravkin; I. N. Bogomolova; S. M. Tsybulin (Сибирский лесной журнал, 2015)
According to the data borrowed from the Biodat base on areas of 536 species of wood plants by means of one of methods of the cluster analysis floristic classification is made and division into districts of Northern Eurasia is executed. Three regions that, in turn, are divided into provinces and districts, are as a result allocated. The border between Southwest and Northeast regions passes diagonally from the northwest on the southeast from the Gulf of Finland of the Baltic Sea to Altai. Such arrangement of border is caused by incomplete postglacial restoration of areas of broad-leaved tree species and modern distinctions in the hydrothermal mode. Considerable similarity of this border with carried out earlier as a result of the similar analysis of fauna of vertebrate animals though on land vertebrata it runs North – from the Kola Peninsula to Baikal is shown. Estimates of communication of variability of communities with various factors of the environment are similar, but usually on land vertebrata they are slightly higher, except for provinciality (35 and 19 % of dispersion). It testifies to more accurate reaction of animals to distinctions in the environment. The exception on provinciality is connected with more coincidence to its accepted gradation on plants (The European, West and East Siberian provinces). It is confirmed by estimates of communication with regionality – division into groups of provinces (regions) that differ on fauna and flora (29 and 38 %) less. The regime explanation of heterogeneity of flora, on the contrary, is slightly fuller, than on fauna (73 and 64 %) though the total assessment on general concepts is approximately identical (80 and 81 % of dispersion).